Refúgio: um mal-estar contemporâneo a experiência dos sírios em São Paulo - Rosal, Anna Silvia Rosal de (2022)
In the last decade, Syria´s civil war has forced over more than 13.3 million people to leave the country in search of protection and freedom. The rupture with culture disorganizes the identity references and leads the person to helplessness. At the same time, the refugee recognizes the desire to leave and the fear of starting over again. In view of this, I understand the refuge as a contemporary discontents. The aim of this research is to understand, from the Psychoanalysis reference, the psychic implications of Syrians refugees living in the city of São Paulo. The research participants constituted a heterogeneous group in terms of age, sex and level of education. In commom, they are affected by the identity stunned and helplessness, among other psychological and cultural fractures. The hope to rebuild the life in a safety and democratic territory is essential to preserve psychic vitality